Narratives of Independent Oil Palm Smallholders on Production Costs, Selling Prices, and Famuly Economic Dynamics - Eva Jannuriati; Ni Made Suwitri Parwati; Andi Ainil Mufidah Tanra (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2026)
This study explores how independent oil palm farmers narrate production costs, fresh fruit bunch (FFB) selling prices, and household economic resilience in Bambalamotu Village, Pasangkayu Regency. A qualitative narrative design with a phenomenological orientation was used to capture farmers' lived experiences rather than to measure economic variables statistically. Data were collected through in-depth interviews, observation, and documentation involving two independent oil palm farmers and two family members who participate in household economic decision-making. The data were analyzed through reduction, thematic categorization, and meaning interpretation. The findings show that rising production costs are experienced not only as operational expenses but also as pressures that reshape household priorities. FFB prices function as the main reference for planning family expenditures, yet price fluctuations create uncertainty because farmers must pay for fertilizer, labor, maintenance, and transport before income is secured. Farmers respond by postponing non-urgent spending, using family labor, organizing collective harvesting arrangements, and diversifying income through other agricultural activities. The novelty of this study lies in showing that independent farmers use cost and price information as informal management accounting knowledge, even without formal records. These findings extend smallholder livelihood and management accounting literature by positioning farmers as active interpreters of economic information and household survival strategies.